AB1125 Prediction of chronic damage in systemic lupus erythematosus by using machine-learning models. (15th June 2017) - Ceccarelli, F; Sciandrone, M; Perricone, C; Galvan, G; Morelli, F; Vicente, LN; Leccese, I; Massaro, L; Cipriano, E; Spinelli, FR; Alessandri, C; Valesini, G; et al.
Abstract : Background: The increased survival in Systemic Lupus Erythematosus (SLE) patients implies the development of chronic damage, occurring in up to 50% of cases after a follow-up of 10 years. Its prevention is a major goal in the SLE management. During the last years, it has been suggested that Artificial Neural Networks (ANNs) could be a useful prediction tool in medical scenarios, by using patients' data as inputs and the specific outcomes as outputs. The International Conference on Advanced Computing and Communication Systems in 2015 underlined the possible application of sophisticated data analysis tools, such as machine learning methods, in SLE patients, in the light of their potential application to diagnostic and prediction purposes. Objectives: In the present study, we aimed at predicting chronic damage in a large monocentric SLE cohort by using neural networks. Methods: For the present analysis, we used data from 413 SLE patients (1997 ACR criteria; M/F 30/383; mean age ± SD 46.3±11.9 years; mean disease duration ± SD 174.6±112.1 months, mean follow-up period ±SD 63.9±30.7 months). At each visit, the patients underwent a complete physical examination and clinical and laboratory data were collected in a standardized, computerized, and electronically filled form. All the patients were evaluated at least twice per year. Autoantibodies and complement serum levels were also registered. Chronic damage was assessed by the SLICC/ACR Damage Index (SDI). We applied Recurrent Neural Networks (RNNs) as a machine-learning model to predict the risk of chronic damage. The clinical data sequences registered for each patient during the follow-up were used for building and testing the RNNs. We used 27 clinical and laboratory items for the mathematical model. Results: At the first visit, 35.8% of patients had an SDI≥1, with a mean±SD value of 1.7±1.1. For the RNN model, two groups of patients were analyzed: patients with SDI=0 at the baseline, developing damage during the follow-up (N=38), and patients without damage (SDI=0). In particular, in the first group, we used all the visits before the development of damage, and in the second group, we considered patients with at least 5 visits and a follow-up of 2 years. We created a mathematical model with an AUC value of 0.77, able to predict damage development. A threshold value of 0.35 (sensitivity 0.74, specificity 0.76) seems able to identify patients at risk to develop damage. Conclusions: We applied RNNs to identify a prediction model for SLE chronic damage. By using longitudinal data, including laboratory and clinical items, we created a mathematical model able to identify patients at higher risk to develop chronic damage. Disclosure of Interest: None declared